Field-based phenotyping for the effects of high night-time temperature stress in wheat and maize - Hein, Nathan T. (Kansas State University, 2022)
Abiotic stresses can differentially alter a plant’s physiology, phenology, yield and quality when coincided with different growth and developmental stages in crops. Along with varying responses due to the time of imposition, the type of abiotic stress (e.g., drought, nutrient, heat, or cold) and the duration of exposure can have differential level of impact. Under a changing climate, increasing temperatures are shown to result in significantly negative impact on crop yield and grain quality. While high day-time temperature stress has been thoroughly researched during the vegetative, reproductive, and grain-filling stages of major crops including wheat (Triticum aestivum L.) and maize (Zea mays L.), the effects of high night-time temperature stress are much less known. The grain-filling period in winter wheat and maize occurs during the summer and hence is hypothesized to be the most susceptible phase to high night-time temperature stress in Kansas under future warming scenarios. As such, this dissertation aims to explore the agronomic and physiological responses, and changes in grain quality and micronutrient composition on exposure to high night-time temperature stress during the grain-filling period of two major cereals grown under field conditions. To address the above objective, the first North American field-based high throughput phenotyping infrastructure for high night-time temperature stress had to be developed. This dissertation will detail the process of developing a small field-based prototype tent system (Chapter 2), the expansion of this methodology into the large field-based infrastructure (Chapter 3), and, finally, the alteration of this methodology to facilitate the phenotyping of large stature crops (Chapter 5). The field-based experiments were successful in applying a dynamic and equally distributed 3.2 ºC and 3.8 ºC high night-time temperature stress in the prototype tents and large field-based infrastructure, respectively. This application of high night-time temperature stress significantly affected the phenology of wheat by advancing the onset of senescence by about 3 days, averaged across 12 different genotypes. The rate of senescence was not affected in maize as the strong stay-green traits in modern hybrids allowed the seeds to reach physiological maturity before the onset of senescence. Agronomically, winter wheat was significantly affected through a reduction in grain yield in both the prototype and large field-based infrastructure (20% and 14%, respectively) as well as a reduction in 200 kernel weight (7% and 5%, respectively). Similarly, high night-time temperature stress on maize resulted in 14% reduction in total yield and an 8% reduction in 200 kernel weight, averaged across 12 commercial hybrids. Seed quality and micronutrient composition was significantly modified due to the application of stress with significant alterations observed in starch, protein, and nutrient content in both winter wheat and maize (Chapter 4 and 5, respectively). Using a susceptible and tolerant maize hybrid, differentially expressed genes governing starch metabolism were analyzed to understand the genomic basis of high night-time temperature resilience for starch synthesis. The evidence for a future climate which is prone to a higher level of variability has been confirmed through extensive climate-based modelling approaches. These predictions paired with the results of our current studies on high night-time temperature stress impacts, provides evidence for warming nights to have a significant negative effect on yield and quality in cereals. This dissertation is a compilation of the first-steps into phenotyping for high night-time stress impacts under field conditions which could be the basis for developing crop varieties/hybrids that can thrive under future uncertain climate.
Keywords: Abiotic stress; Agronomy; Heat stress; Wheat; Maize